1988
DOI: 10.1111/j.1469-8749.1988.tb04795.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Risk Factors and Later Neurodevelopmental Disturbances

Abstract: SUMMARY Background factors of developmental outcome in a group of 386 neonatal ‘at‐risk’ infants and 107 controls were examined in a prospective nine‐year follow‐up study. Dichotomized outcome variables were computed for each of the assessments; neurodevelopmental, motor, psycholinguistic, cognitive and school progress. In the study group, 17 to 29 per cent were found to have significant problems, compared with 10 to 17 per cent of the control group. Children with low birthweight, neonatal neurological symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…[28] This test is used in children of age between 5 and 9 years. This examination consists of 21 tasks.…”
Section: Methodsmentioning
confidence: 99%
“…[28] This test is used in children of age between 5 and 9 years. This examination consists of 21 tasks.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis demonstrated an association between increased impairment and low birthweight. 139 Also in Finland, parental questionnaires completed on over 8000 eight-year-old children in the North Finland Birth Cohort indicated that those born <2500g were poorer in motor skills than the rest of the cohort. 140 An ingenious study examined, at age nine years, 22 pairs of twins who had had a birth weight difference between the pair of at least 25%.…”
Section: Obstetric and Neonatal Outcomesmentioning
confidence: 99%
“…These include intrinsic factors such as perinatal insults [6][7][8]; gestational age at birth [9][10][11] and altered neurological pathways [3,5]; low birthweight [12][13][14][15][16][17]; disease processes and severity [18][19][20]; genetic and epigenetic factors including sociocultural influences [17,21], language exposure [22][23][24] and developmental interaction [25][26][27][28]; and nosocomially derived factors such as adverse environmental exposures [29,30], sepsis and neurotoxicity from drugs [31,32]. Long-term studies on language outcomes in preterm infants reveal delays in various aspects of receptive and expressive language [13,14], articulation, comprehension [25], oromotor skills and spontaneous speech [33].…”
Section: Introductionmentioning
confidence: 99%